2020
DOI: 10.3390/pathogens9030187
|View full text |Cite
|
Sign up to set email alerts
|

Different Cell Wall-Degradation Ability Leads to Tissue-Specificity between Xanthomonas oryzae pv. oryzae and Xanthomonas oryzae pv. oryzicola

Abstract: Xanthomonas oryzae pv. oryzae (Xoo) and Xanthomonas oryzae pv. oryzicola (Xoc) lead to the devastating rice bacterial diseases and have a very close genetic relationship. There are tissue-specificity differences between Xoo and Xoc, i.e., Xoo only proliferating in xylem vessels and Xoc spreading in intercellular space of mesophyll cell. But there is little known about the determinants of tissue-specificity between Xoo and Xoc. Here we show that Xoc can spread in the intercellular spaces of mesophyll cells to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Paenibacillus genus was isolated from human and environmental samples [47]. Xanthomonas shows cellulose structure degradation activity [48]. Stenotrophomonas was isolated and identified from an oil painting on canvas, which showed visible signs of biodeterioration [49].…”
Section: Molecular Characterization Of Microbial Community (Fungi And...mentioning
confidence: 99%
“…Paenibacillus genus was isolated from human and environmental samples [47]. Xanthomonas shows cellulose structure degradation activity [48]. Stenotrophomonas was isolated and identified from an oil painting on canvas, which showed visible signs of biodeterioration [49].…”
Section: Molecular Characterization Of Microbial Community (Fungi And...mentioning
confidence: 99%
“…Double asterisks (** P < 0.01) stand for the significant difference between floating and pre-planting tobacco at the same day under cold stress freezing tolerance of pea (Lucau-Danila et al 2012). Normal cell wall under transmission electron microscope was shown as the layer of structure with low electrondensity, but the cell wall broken by biotic stress was reported to have high electron-density because of the deposition of osmiophilic material in cell wall (Cao et al 2020). These results from the present study showed slightly thicker cell wall in the leaf mesophyll and root cortical cells from pre-planting tobacco than cells from floating tobacco before cold stress (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it can spread into intercellular spaces of mesophyll cells to induce streak lesions along the veins. 4,5 However, to the best of our knowledge, only a handful of examples of the preparation of bioactive molecules for controlling Xoc are reported to date. [6][7][8][9][10][11][12][13][14] On the other hand, Verticillium dahlia is a soil-borne fungus that invades the plants via their roots.…”
Section: Introductionmentioning
confidence: 99%
“…The bacterium of Xoc enters rice leaves via wounds/stomata and colonizes in the sub‐stomatal cavities. Meanwhile, it can spread into intercellular spaces of mesophyll cells to induce streak lesions along the veins 4,5 . However, to the best of our knowledge, only a handful of examples of the preparation of bioactive molecules for controlling Xoc are reported to date 6–14 .…”
Section: Introductionmentioning
confidence: 99%